Targeting mucus barrier in respiratory diseases by chemically modified advanced delivery systems. (25th September 2022) - Prasher, Parteek; Sharma, Mousmee; Singh, Sachin Kumar; Gulati, Monica; Jha, Niraj Kumar; Gupta, Piyush Kumar; Gupta, Gaurav; Chellappan, Dinesh Kumar; Zacconi, Flavia; de Jesus Andreoli Pinto, Terezinha; Chan, Yinghan; Liu, Gang; et al.
Abstract: Mucus gel constitutes of heavily cross-linked mucin fibers forming a viscoelastic, dense porous network that coats all the exposed epithelia not covered with the skin. The layer provides protection to the underlying gastrointestinal, respiratory, and female reproductive tracts, in addition to the organs such as the surface of eye by trapping the pathogens, irritants, environmental fine particles, and potentially hazardous foreign matter. However, this property of mucus gel poses a substantial challenge for realizing the localized and sustained drug delivery across the mucosal surfaces. The mucus permeating particles that spare the protective properties of mucus gel improve the therapeutic potency of the drugs aimed at the management of diseases, including sexually transmitted infections, lung cancer, irritable bowel disease, degenerative eye diseases and infections, and cystic fibrosis. As such, the mucoadhesive materials conjugated with drug molecules display a prolonged retention time in the mucosal gel that imparts a sustained release of the deliberated drug molecules across the mucosa. The contemporarily developed mucus penetrating materials for drug delivery applications comprise of a finer size, appreciable hydrophilicity, and a neutral surface to escape the entrapment within the cross-inked mucus fibers. Pertaining to the mucus secretion as a first line of defence in respiratory tract in response to the invading physical, chemical, and biological pathogens, the development of mucus penetrating materials hold promise as a stalwart approach for revolutionizing the respiratory drug delivery paradigm. The present review provides an epigrammatic collation of the mucus penetrating/mucoadhesive materials for achieving a controlled/sustained release of the cargo pharmaceutics and drug molecules across the respiratory mucus barrier. Graphical abstract: Image 1 Highlights: Role of mucosal layer in impeding respiratory drug delivery. Role of charge on drug delivery system for the mucosal delivery. Chemical modifications of polysaccharides and polymers for effective mucosal drug delivery. Advanced delivery systems for drug delivery across mucosal layers.